Finding your roots with Henry Louis Gates, Jr. Season 7 [videorecording (DVD)] - Streeter, Sabin; Streeter, Sabin; Whetstone, Krista; Gates, Henry Louis, Jr; Gates, Henry Louis, Jr; Close, Glenn, 1947-; Cohen, Andy, 1968- ([publisher not identified], 2021)
Dr. Gates uses genealogy and DNA science to trace the ancestry of celebrities.